Data collection tool to successfully apply the Kaleidoscope model of policy change - Ouerghemmi, Hassen; M. Oumer, Ali; Dhehibi, Boubaker; Frija, Aymen (International Center for Agricultural Research in the Dry Areas, 2024)
The interview tool is designed to effectively capture the information necessary for the practical application of the Kaleidoscope Model to policy change. That is why this structured interview framework includes a set of specific triangulated questions focused on key policy parameters such as context, actors, processes, and results. Each question in the interview serves to facilitate explaining potential determinants of the policy adoption and implementation, allowing for a comprehensive understanding of ongoing processes.